MANAGEMENT OF FACILITIES AND INFRASTRUCTURE IN SUPPORTING PROJECT-BASED LEARNING STRENGTHENING THE PANCASILA STUDENT PROFILE (P5) AT SMP NEGERI 2 GATAK - AISYAH, PUTRI NUR; MUFASIROH, QORI'ATUL; ASTUTI, WIDYA AYU; NUROHIM, MUHAMMAD ALDI; P, HELDY RAMADHAN PUTRA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The Pancasila Student Profile Strengthening Program (P5) is one of the programs in the implementation of the Independent Curriculum. This program is a project-based co-curricular activity that aims to encourage students to become competent, character-based lifelong learners who behave in accordance with Pancasila values ??to achieve Graduate Competency Standards. With this background, this study aims to identify the influence of facility and infrastructure management in supporting learning based on the Pancasila Student Profile Strengthening Project (P5) at SMP Negeri 2 Gatak. The method used is a qualitative approach with data collection through observation, interviews, and documentation. The results of the study indicate that there is an influence and challenge of facility and infrastructure management in supporting project-based learning that can contribute to the evaluation and impact on the quality of learning. In addition, collaboration between teachers, schools, and parents of students has also proven important to increase the effectiveness of the use of facilities and infrastructure. With the Improvement of facility and infrastructure management to support the success of the P5 program, as well as the development of teacher competencies in the implementation of the independent curriculum, it is hoped that it can focus on strengthening character and active involvement of students. ABSTRAKProgram Penguatan Profil Pelajar Pancasila (P5) adalah salah satu program dari implementasi Kurikulum Merdeka. Program ini merupakan kegiatan kokurikuler berbasis projek yang bertujuan untuk mendorong peserta didik menjadi pelajar sepanjang hayat yang kompeten, berkarakter, dan berperilaku sesuai dengan nila-nilai pancasila untuk mencapai Standar Kompetensi Lulusan. Dengan latar belakang tersebut, penelitian ini bertujuan untuk mengidentifikasi pengaruh manajemen sarana dan prasarana dalam mendukung pembelajaran berbasis Projek Penguatan Profil Pelajar Pancasila (P5) di SMP Negeri 2 Gatak. Metode yang digunakan adalah pendekatan kualitatif dengan pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa terdapat pengaruh dan tantangan manajemen sarana dan prasarana dalam mendukung pembelajaran berbasis projek dapat berkontribusi terhadap evaluasi dan dampak pada kualitas pembelajaran. Selain itu, kolaborasi antara pihak guru, sekolah, maupun orang tua siswa juga terbukti penting untuk meningkatkan efektivitas penggunaan sarana dan prasarana. Dengan adanya Peningkatan pengelolaan sarana dan prasarana untuk mendukung keberhasilan program P5, serta pengembangan kompetensi guru dalam implementasi kurikulum merdeka, diharapkan dapat fokus pada penguatan karakter dan keterlibatan aktif siswa.